2015
DOI: 10.1177/1550059415605686
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Visual Short-Time Neurofeedback on Brain Activity and Clinical Characteristics in Alcohol Use Disorders

Abstract: The present study was carried out to examine the efficacy of alpha/theta neurofeedback (NF) with a new visual paradigm in a cohort of alcohol use disordered (AUD) patients (n = 25) treated in an Austrian therapeutic community center. The experimental study design focused on changes in absolute and relative resting EEG band power as well as in clinical variables, including depression (Beck Depresion Inventory [BDI-V]), psychiatric symptoms (Brief Symptom Inventory [BSI], coping (Freiburg Questionnaire on Coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 48 publications
1
36
0
3
Order By: Relevance
“…The Peniston and Kulkosky study ( 1989 ) developed the alpha-theta protocol and found more sustained prevention of relapse (defined as not using alcohol for more than 6 contiguous days) in 13-months follow up in alcohol addicted patients who were treated with EEG neurofeedback as add-on treatment compared to patients who only received standard treatment. However, a later study by Lackner et al ( 2016 ) who also used the theta-alpha protocol found no effects on craving or on the 5-month follow up assessment in a group of alcohol addicted in-clinic patients. This same protocol was used in opioid users add-on to psychopharmacological treatment, where they found reduced craving compared to the group that only received medication (Arani et al 2010 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The Peniston and Kulkosky study ( 1989 ) developed the alpha-theta protocol and found more sustained prevention of relapse (defined as not using alcohol for more than 6 contiguous days) in 13-months follow up in alcohol addicted patients who were treated with EEG neurofeedback as add-on treatment compared to patients who only received standard treatment. However, a later study by Lackner et al ( 2016 ) who also used the theta-alpha protocol found no effects on craving or on the 5-month follow up assessment in a group of alcohol addicted in-clinic patients. This same protocol was used in opioid users add-on to psychopharmacological treatment, where they found reduced craving compared to the group that only received medication (Arani et al 2010 ).…”
Section: Resultsmentioning
confidence: 93%
“…In most studies short treatment courses were used: fMRI neurofeedback studies (max 3), tDCS (max 10), rTMS (max 16), only in EEG neurofeedback four studies used 30 sessions or more. This might have contributed to the lack of long-term effects found by several studies: Da Silva et al ( 2013 ) with 5 sessions, Amiaz et al ( 2009 ) with 16 sessions, Trojak et al ( 2015 ) with 10 sessions and Lackner ( 2016 ) with 12 sessions. It is likely that in order to change neural programs and their associated behavior, extensive practice is needed using more sessions.…”
Section: Discussionmentioning
confidence: 99%
“…EEG data was processed using Matlab software and artifacts were removed manually. The details of the EEG acquisition and the precise technical background of NF application are described in our previous paper (Lackner et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore hypothesized that especially personality traits linked to lacking control experience and the stress reactivity pathway (avoidant and dependent traits including Neuroticism) would change through the intervention. The patients, together with the treatment procedure in this study, were the same as those contained in our previous report focussing on changes in brain activity (Lackner et al, 2015 ). This paper examines a different set of measures on the subjects with an elaborated focus on changes in Personality Accentuations related to the DSM-personality disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Zahlreiche Studien finden sich über die erfolgreiche Anwendung von NFB bei psychiatrischen Patienten, unter anderem bei der Behandlung von Abhängigkeitserkrankungen [16] oder dem Aufmerksamkeitsdefizit-Hyperaktivitäts-Syndrom (ADHS) [17]. In einer Studie an männlichen Suchtpatienten konnten wir bereits nachweisen, dass NFB zu symptomatischen Verbesserungen führt und sich Hirnaktivierungsmuster dadurch verändern lassen [18]. Unter kombinierter Behandlung von Psychotherapie und Training der langsamen Hirnpotenziale konnten wir in einer Einzelfallstudie bei einem alkoholabhängigen Patienten eine Abnahme von Anhedonie und Entfremdungsgefühlen zeigen [19].…”
unclassified